Communication competence and disability secondary to laryngectomy and tracheoesophageal puncture voice restoration. Issue 2 (11th November 2022) - Doyle, Philip C.; Baker, Adrienne M. H.; Evitts, Paul M.
Abstract: Background: There is a large body of research showing the negative impact of a total laryngectomy on the resultant voice signal across multiple outcomes (e.g., speech intelligibility/acceptability, listener comprehension, voice quality). However, there is limited information on the effects of laryngectomy on broader communication acts, particularly in the area of pragmatics, commonly referred to as the social use of language. Considering that individuals with a laryngectomy (IWL) frequently report reduced quality of life as well as reduced communicative competency, expanding the current research to include pragmatics is warranted. Aim: To explore the pragmatic changes in communication experienced by tracheoesophageal speakers. Methods & Procedures: The current study adapted an existing 17‐item measure to assess verbal, non‐verbal, paralinguistic and receptive communication competence via self‐report. This adapted measure was then distributed to 65 tracheoesophageal speakers (52 males, 13 females, mean age = 63.4 ± 8.5 years). Outcomes & Results: Both negative and positive pragmatic changes to communication were reported by participants secondary to laryngectomy. This included changes in verbal (negative –37.5%, positive –15.15%); non‐verbal (negative –9.54%, positive –35.45%; and paralinguistic acts (negative –29.55%, positive –34.09%). Changes to receptive communication were also noted (negative –14.78%, positive –43.19%). Conclusions & Implications: The overall results suggest that communication changes post‐laryngectomy exist well beyond the paralinguistic areas (e.g., intelligibility, voice quality) and that males and females may approach or respond to changes in communication differently. Results are discussed specific to clinical intervention and the importance of including assessment of pragmatic function post‐laryngectomy. WHat this paper adds: What is already known on this subject: While there is a large body of research on the changes to the speaker and listener following laryngectomy, there is minimal information on how the use of alaryngeal speech affects overall communication, specifically in the area of pragmatics or the social use of language. What this paper adds to existing knowledge: This study used an adapted version of the widely used Pragmatic Protocol to delineate changes in pragmatic components of communication for tracheoesophageal speakers. What are the potential or actual clinical implications of this work?: Clinically, this information can be used by healthcare professionals to educate and prepare IWL on potential changes in the underrecognized area of pragmatics.